The Relationship between Teacher`S Knowledge of the Commerce Learning Experience and Evaluation and the Teacher`S Management of the Implementation of the Commerce in Secondary Schools, Kuala Lumpur - Awi, Asnaini (2008)
This study aims to identify the relationship between teachers’ knowledge of commerce learning experience and evaluation and the teachers’ management of the implementation of the commerce instruction in secondary schools in Kuala Lumpur. The subjects consists of 30 commerce teachers from different schools in the Pudu Zone of Kuala Lumpur. Two research instruments namely, the Commerce Knowledge Test used to measure the teachers’ knowledge of the commerce learning experience and evaluation; and a questionnaire, used to measure the level of implementation management of the commerce instruction, are utilised. The findings of the research are reported based on six questions. Firstly, how far do the commerce teachers actualy know the commerce learning experience based on the learning experience specifications and teaching methods; and commerce evaluation? Secondly, how far do the commerce teachers manage to implement the instruction from the perspective of management of teaching, classroom management and the management of commerce test? Thirdly, is there any relationship between teachers’ knowledge of the commerce learning experience and evaluation and the teachers’ management of the commerce instruction implementation? Fourthly, is there any relationship between teachers’ knowledge of the learning experience and the demographic factors such as teaching options, experience in teaching the subject, academic qualifications and experience in marking SPM examination paper? Fifth, what are the problems faced by commerce teachers in implementing the instruction? Sixth, what are the possible suggestions made by the commerce teachers in order to overcome the existing problems? The results showed that teachers’ level knowledge of the commerce learning experience and evaluation is moderate (mean score = 67.93, standard deviation = 19.73), meanwhile the level of the commerce instruction implementation management is moderate (mean score = 147.57, standard deviation = 13.30). The results also showed that a no significant relationship exist between teachers’ knowledge of the learning experience and the implementation of the instruction based on three aspects, namely management of teaching (r = -0.070, p ≥ 0.05), classroom management (r = 0.018, p ≥ 0.05) and test management (r = 0.039, p ≥ 0.05). The results also showed that a no significant relationship between teachers’ knowledge of the commerce learning experience and the demographic factors; namely teaching options (rcc = 0.534, p ≥ 0.05), teaching experience (r = -0.198, p ≥ 0.05), academic qualifications (rs = -0.094, p ≥ 0.05) and experience as SPM examination paper examiner (r = -0.053, p ≥ 0.05). The results of data analysis on the problems and challenges faced by commerce teachers in managing the commerce instruction implementation showed that most respondents have problems with the uncoordinated learning experience specifications and as well as limited time to finish up the syllabus. Most respondents suggested that the learning experience specifications should be simplified and extra teaching time should be given. In conclusion, even though there is no significant relationship between the teachers’ knowledge of the commerce learning experience and evaluation and the teachers’ implementation management of the commerce instruction and also the no significant relationship between the teachers’ knowledge of the commerce and demographic factor, all of the problems faced by the teachers and their suggestions need to be taken into considerations by responsible parties in order to find solutions to the real factors that have caused the decline of the students’ performance in the commerce subject among secondary students in Kuala Lumpur.